The Montreal Cognitive Assessment (MoCA): updated norms and psychometric insights into adaptive testing from healthy individuals in Northern Italy - Aiello, Edoardo Nicolò; Gramegna, Chiara; Esposito, Antonella; Gazzaniga, Valentina; Zago, Stefano; Difonzo, Teresa; Maddaluno, Ottavia; Appollonio, Ildebrando; Bolognini, Nadia (Aging clinical and experimental research, 2022)
Background The availability of fine-grained, culture-specific psychometric outcomes can favor the interpretation of scores of the Montreal Cognitive Assessment (MoCA), the most frequently used instrument to screen for mild cognitive dysfunctions in both instrumental and non-instrumental domains. This study thus aimed at providing: (i) updated, region-specific norms for the Italian MoCA, by also (ii) comparing them to pre-existing ones with higher geographical coverage; (iii) information on sensitivity and discriminative capability at the item level. Methods Five hundred and seventy nine healthy individuals from Northern Italy (208 males, 371 females; age: 63.4 ± 15, 21–96; education: 11.3 ± 4.6, 1–25) were administered the MoCA. Item Response Theory (IRT) was adopted to assess item difficulty and discrimination. Normative values were derived by means of the Equivalent Scores (ESs) method, applied to the MoCA and its sub-scales. Average ESs were also computed. Agreement with previous ESs classification was assessed via Cohen’s k . Results Age and education significantly predicted all MoCA measures except for Orientation, which was related to age only. No sex differences were detected when tested along with age and education. Substantial disagreements with previous ESs classifications were detected. Several items proved to be scarcely sensitive, especially the place item from Orientation and the letter detection task. Memory items showed high discriminative capability, along with certain items assessing executive functions and orientation. Discussion Item-level information herewith provided for the Italian MoCA can help interpret its scores by Italian practitioners. Italian practitioners should consider an adaptive use of region-specific norms for the MoCA.